Eli Mule Noa's Quiet Tradition: A Socio-Theological Study of the Social Adhesion of Youth of the Ebenhaizer Apuri-Alor Church - Sri Yulianti B. Atacay; Rama Tulus Pilakoannu (CV. Rayyan Dwi Bharata, 2023)
This study aims to analyze the causes of the fading of Tenang Eli Mule Noa as a social cohesion among the youth of Ebenhaizer Pura Apuri and describe the church's efforts in reviving Calm Eli Mule Noa as a social cohesion among youth. Research methods use socio-theological studies because they have a variety of knowledge that can be a guide to preserve existing culture. Socio-theological studies provide knowledge of social processes that allow one to gain an understanding of the dynamic movement of society. The results showed Calm Eli Mule Noa the philosophy of the temple community which in its development succeeded in realizing love, joy, peace, gentleness, and also self-mastery in the life of the Apuri community.